A versatile X‐ray phase retarder for lock‐in XMCD measurements. (6th August 2020) - Poldi, Eduardo H. T.; Escanhoela Jr, Carlos A.; Fonseca Jr, Jairo; Eleotério, Marcos A. S.; dos Reis, Ricardo D.; Lang, Jonathan C.; Haskel, Daniel; Souza-Neto, Narcizo M.
Abstract : A versatile strategy to perform efficient X‐ray magnetic circular dichroism experiments with a quarter‐wave plate using a setup that combines non‐conventional dispersive optics with locked‐in acquisition, also compatible with monochromatic X‐ray beamlines and large magnets, is reported. Abstract : X‐ray magnetic circular dichroism (XMCD) is a technique commonly used to probe magnetic properties of materials with element and orbital selectivity, which requires the use of circularly polarized (CP) X‐rays. It is possible to accomplish XMCD experiments with fixed CP and alternating the magnetic field orientation, but most reliable data are obtained when alternating the magnetization orientation and the polarization between right and left helicities. A versatile strategy has been developed to perform XMCD experiments using a hard X‐ray quarter‐wave plate, at both polychromatic dispersive and conventional monochromatic optics, in combination with synchronous data acquisition. The switching frequency waveform is fed into a lock‐in amplifier to detect and amplify the XMCD signal. The results on a reference sample demonstrate an improvement in data quality and acquisition time. The instrumentation successfully generated 98% of CP X‐rays switching the beam helicity at 13 Hz, with the possibility of faster helicity switching once it is installed at the new Brazilian fourth‐generation source, SIRIUS.